INTEGRASI NILAI-NILAI MODERASI BERAGAMA DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH UMUM - Ratna Sari; Titi Kadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the strategy of integrating the values of religious moderation in the subject of Islamic Religious Education (PAI) in public schools in Indonesia. The main problem raised is the increasing vulnerability of students to radicalism and intolerance in the school environment triggered by exclusive religious understanding. The importance of this research lies in the urgency of strengthening religious moderation as a pillar of national stability in a multicultural society. The methodology used is qualitative research with a literature study approach and case study analysis in several high schools. The results of the study show that integration is carried out through an explicit approach in the curriculum and an implicit approach through school culture and the role of teachers as role models. The "Peace School" strategy and planned implementation management from planning to evaluation have proven effective in shaping the character of students who are tolerant, inclusive, and respectful of cultural diversity according to the Islamic principles of wasathiyyah.